Study on Human Resource Management in Agriculture - Zalainé Piros, Márta (Acta Agraria Debreceniensis, 2002)
The human factor has been reassessed with regard to strategic initiatives towards obtaining and preserving competitive advantage. Knowledge, experience and special skills are a specific form of capital, forming part of the organisations’ assets and serving as an organisational strategic resource. Their development and use require major investments, both on the part of the individual and the organisation. In a Europe undergoing integration, the quality of human resources enjoy priority among our really important values and specific features. The opportunities of the near future can be utilised, and agricultural economic organizations can survive and increase their organizational effectiveness, if they possess a basis of human capital which is able to make a shift in perspective and behaviour which is of primary importance from the point of view of incorporating market mechanisms and implementing them in practice. My investigations were focused on the current position of human resource management in a comprehensive manner; further, on the approach of top managers regarding the future. Analysing the business and other indicators of the companies studied, I have set the objective to describe the differences and special features of the human resource management practice of companies, which are different in size, operational form, and from the perspective of success or failure.Human resource management is directed to attracting, retaining, motivating and utilising labour. A given work process can be successful or unsuccessful – given the same conditions – depending on who performs it. Therefore, human resource management related tasks require special attention when enterprises are planned, established and operated. On analysing the responsibilities of human resource management, I have found that the functions and responsibilities of human resource have low or medium importance in the operation of economic organisations today. Regarding the future, top managers have expressed higher expectations of human resource management responsibilities in all areas and they consider individual functions to be more important. The establishment and operation of a human resource information system has been presented as the most important need for change. Correlation analyses have proved that the higher the sales revenues of a company, the higher the development of human resources is regarded by its manager, and the same holds for training, career support and a proper establishment and continuous evaluation of job profiles.